Is a gender-morality or gender-control gap responsible for male-female differences in delinquency? cross-sectional and longitudinal analyses - Walters, Glenn D. (Journal of crime and justice, 2024)
This study tested for gender-morality and gender-control gaps that might explain sex differences in crime in a group of 2,718 early adolescent youth (1,309 boys and 1,409 girls; mean age = 12.12 years). Although moral neutralization and cognitive impulsivity were significantly higher in boys than in girls and moral neutralization rose significantly over time, the rise was roughly comparable across gender. Analyses confirmed the presence of a gender-morality gap whereby moral neutralization had an effect on delinquency in boys but not girls, and a gender-control gap where cognitive impulsivity played a role in delinquency for girls but not boys. In a cross-sectional analysis, the partial correlation between gender and moral neutralization, controlling for delinquency, was significantly higher than the partial correlation between gender and delinquency, controlling for moral neutralization, implying that gender differences in moral neutralization are stronger than gender differences in delinquency in early adolescence. In a longitudinal analysis, moral neutralization mediated the relationship between gender and delinquency in a design with proper temporal order between the independent (gender), mediating (moral neutralization), and dependent (delinquency) variables. These findings suggest that weak moral agency may be one of the factors driving the well-known relationship between male gender and antisocial behavior.